Developing financial leadership in small-medium businesses - Barnes, Stewart; Prowle, Malcolm (Routledge, 2025)
"Many small-medium enterprises (SMEs) are very small organisations comprising mainly of single-person and micro-businesses but, in the UK, there are around 250,000 small-medium businesses (SMBs) which are substantial businesses with turnovers of millions or tens of millions of pounds. A key requirement for thriving SMBs is effective leadership throughout the organisation. One crucial aspect, which is often overlooked, is that of financial leadership. Financial management in SMBs is often seen as a technique-based activity whereby finance staff have a limited role preparing annual financial accounts and disseminating financial information to key individuals in the organisation. They may act reactively by responding to requests for specific financial information. On the other hand, strong financial leadership is proactive, constructive, innovative and plays a critical role in ensuring that organisations stay financially adaptable and can build resilience and sustainability in today's fierce market. The most effective financial leaders have a sophisticated and thorough understanding of their organisation's financial health, and they make decisions grounded in financial realities to use that information in their communication to demonstrate the strategic connection between money, mission and purpose. This research volume asserts that understanding the importance of utilising robust financial management approaches and financial information in making business decisions and assessing business performance is key. This is especially relevant for SMBs, as they can have a significant influence on country economies. It will therefore be of interest to researchers, academics, practitioners, and advanced students in the fields of leadership, financial management, entrepreneurship, and strategy"-- Provided by publisher.
Keywords: Leadership.; Business enterprises -- Finance.; Industrial management.; Small business -- Management.; elektronické knihy; electronic books